REUSE OF SLUDGE FROM PULP AND PAPER-INDUSTRY PILOT AND FULL-SCALE APPLICATIONS - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1993)
Recent advances made in the reuse of pulp and paper industry sludges in hardboard production are explained. Data obtained from pilot and full-scale plants using primary sludge of a pulp and paper industry as an additive in the production of hardboard is presented. An economic analysis of the reuse of pulp and paper primary sludge in hardboard manufacturing is given. The quality of the hardboard produced is tested and compared with the qualities of the hardboard produced by the same plant before the addition of primary sludge. The hardboard with primary sludge additive has been used in Turkey for about a year in the manufacturing of office and home furniture. The results are very satisfactory when the primary sludge is used at 1/4 ratio.
Keywords: PRIMARY SLUDGE; HARDBOARD; REUSE; SLUDGE UTILIZATION